Conservative Management of Hyperferritinemia in Hemolytic Disease of the Fetus and Newborn: A Case Report and Review of the Literature. Issue 2 (18th March 2021) - Adam, Danielle L.; Bowes, Lynette; Goodyear, Lisa; Moorehead, Paul C.
Abstract : We report a newborn with hemolytic disease of the fetus and newborn (HDFN) with rapid resolution of extreme hyperferritinemia without chelation. An infant born at 35+3 weeks with HDFN and a history of 3 intrauterine transfusions developed severe hyperferritinemia (maximum, 8258 mcg/L) without evidence of toxic iron deposition on liver biopsy. Her hyperferritinemia was managed with observation alone, and ferritin levels normalized rapidly. This case supports observation as being the preferred alternative to chelation therapy for significant hyperferritinemia in newborns with HDFN in the absence of demonstrated toxic end-organ iron deposition. We also include a review of the related available literature.